A~New Social Conflict on Globalisation-Related Issues in Germany? A~Longitudinal Perspective - Céline Teney; Li Kathrin Rupieper (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2023)
We draw on cleavage theory to assess the emergence of a~social conflict concerning globalisation-related issues among the German population between 1989 and 2019. We argue that issue salience and opinion polarisation are key conditions for a~successful and sustainable political mobilisation of citizens and thus for the emergence of a~social conflict. In line with globalisation cleavage theory, we hypothesised that issue salience as well as overall and between-group opinion polarisation on globalisation-related issues have increased over time. Our study considers four globalisation-related issues: immigration, the European Union (EU), economic liberalism, and the environment. While the salience of the EU and economic liberalism issues remained low during the observed period, we found a~recent increase in salience for the issues of immigration (since 2015) and the environment (since 2018). Furthermore, our results point to rather stable attitudes on globalisation-related issues among the German population: We did not find any consistent evidence of an increase in overall or between-group polarisation over time. In conclusion, the idea of an emerging conflict around globalisation-related issues among the German population finds very little empirical support.
Keywords: 300; Globalisation cleavage; Opinion polarisation; Issue salience; Attitudes; German population; Longitudinal analysis; Globalisierungs-Cleavage; Meinungspolarisierung; Themensalienz; Einstellungen; Deutsche Bevölkerung; Längsschnittanalyse